Public Perception about Social Work Profession - Osmanaga, Fatbardha (European Journal of Sustainable Development, 2019)
The perception of social work profession is very important, because there are people that are beneficiaries of social services. So, if we have positive perceptions, will have a strong relationship between social workers and people and the quality of services will be better.We have a quantitative study. The main purpose of the paper is to know the public information and perception about the social work profession. The research questions of the paper are:1.What is the information of Shkodra citizens regarding the social work profession?2.What is the perceptionof Shkodra citizens about the social work profession?3.What is the opinion of Shkodra citizens regarding the areas of social work?4.What is the opinion of Shkodra citizens regarding the roles of the social worker?The population of the study is composed of residents of the city of Shkodra. The sampling consists of people who have reached the age of 18. It is sed the survey method. A questionnaire composed of four parts is used. The first part includes the demographic data of the participants, the second part includes data about the information of participants for social work profession, the third part includes data related to the perception that they have regarding social work profession and the fourth part includes data about the opinion of the participants for the fields and roles of the social workers.The syrvey was created on the basis of different sources. There are given the coclusions and the appropriate suggestions. Keywords: Shkodra city, social work, public perception.